Efficacy and safety of thrombus aspiration in ST-segment elevation myocardial infarction: an updated systematic review and meta-analysis of randomised clinical trials. Issue 1 (February 2019) - Taglieri, Nevio; Bacchi Reggiani, Maria Letizia; Ghetti, Gabriele; Saia, Francesco; Compagnone, Miriam; Lanati, Gianluca; Di Dio, Maria Teresa; Bruno, Antonio; Bruno, Matteo; Della Riva, Diego; Corsini, Anna; Narducci, Riccardo; et al.
Background: The role of thrombus aspiration plus primary percutaneous coronary intervention in ST-segment elevation myocardial infarction remains controversial. Methods: We performed a meta-analysis of 25 randomised controlled trials in which 21, 740 ST-segment elevation myocardial infarction patients were randomly assigned to thrombus aspiration plus primary percutaneous coronary intervention or primary percutaneous coronary intervention. Study endpoints were: death, myocardial infarction, stent thrombosis and stroke. Results: On pooled analysis, the risk of death (4.3% vs. 4.8%, odds ratio (OR) 0.90, 95% confidence interval (CI) 0.79–1.03; P =0.123), myocardial infarction (2.4% vs. 2.5%, OR 0.95, 95% CI 0.80–1.13; P =0.57) and stent thrombosis (1.3% vs. 1.6%, OR 0.80, 95% CI 0.63–1.01; P =0.066) was similar between thrombus aspiration plus primary percutaneous coronary intervention and primary percutaneous coronary intervention. The risk of stroke was higher in the thrombus aspiration plus primary percutaneous coronary intervention than the primary percutaneous coronary intervention group (0.84% vs. 0.59%, OR 1.401, 95% CI 1.004–1.954; P =0.047). However, on sensitivity analysis after removing the TOTAL trial, thrombus aspiration plus primary percutaneous coronary intervention was not associated with an increased risk of stroke (OR 1.01, 95% CI 0.58–1.78). The weak association between thrombus aspiration and stroke was also confirmed by the fact that the lower bound of the 95% CI was slightly below unity after removing either the study by Kaltoft or the ITTI trial. There was no interaction between the main study results and follow-up, evidence of coronary thrombus, or study sample size. Conclusions: In patients with ST-segment elevation myocardial infarction, thrombus aspiration plus primary percutaneous coronary intervention does not reduce the risk of death, myocardial infarction or stent thrombosis. Thrombus aspiration plus primary percutaneous coronary intervention is associated with an increased risk of stroke; however, this latter finding appears weak.